Potensi Limbah Pertanian Indonesia sebagai Agen Antidiabetes: Studi Kasus Rambut Jagung dan Kulit Jeruk - Wenny; Aning Ayucitra (Universitas Katolik Musi Charitas, 2019)
Agricultural by-products such as corn silk and kaffir limepeels have not been utilized well. Since every part of a plant contains phenolicscompounds as a result of their secondary metabolism, it is possible that these two wastes can be used as a source of natural antioxidants. Therefore in this study, we investigated the phenolic content in corn silk and citrus peel and assess the ability of the extracts to reduce the conversion of starch to sugar in antidiabetic assessment. Research procedures include raw materialpreparation, extraction, activity assessment and loading the extract into the nanomaterialpores. The results showed that corn silk and kaffir lime peels have different total phenolic contents. Specifically for corn silk, it can be seen clearly that the plant varietycontribute to the amount of total phenolic content. Corn silk from P11 variety has the largest phenolic content up to 1.58 mg GAE/g. Therefore this materialexhibited the highest antioxidant activity against DPPH free radicals, but it has a relatively low for antidiabetic activity. For citrus, this study showed that peels of lemon, lime and kaffir lime exhibited different content of phenolicswith kaffir lime peels extract had the highest phenolics, up to 23.36 mg GAE/g, while the extract of lemon and lime peels were 7.94 and 9.71 mg GAE/g, respectively. In addition, extract of kaffir lime peels has the highest phenolics content compared to other parts such as leaves and juice. The use of different solvents provides different antidiabetic activity. The loading of kaffir lime peels extract into nanomaterial pores was successful, promising future application in the field of drug delivery. However, other studies are still required to improve the effectiveness of diabetes therapy using natural products.